Does FX derivative usage improve firm value? An investigation of non-financial UK firms - Mohan, Prashanth (2017)
This paper investigates whether FX derivative usage improves firm value using a sample of 370 non-financial UK firms for the period of 2015 to 2016. In univariate tests, we find that, on average, the firm value of FX derivative users is marginally greater than non-users, but ultimately this difference is not statistically significant. In our initial pooled OLS specification, we find that FX derivative usage covets an economically and statistically significant value premium, which suggests that on average, an FX derivative user has a 5.35% greater firm value when compared to a non-user, ceteris paribus. However, we find that this value premium is sensitive to the effect of outliers and when addressing key elements of omitted variable endogeneity by controlling for the effect of industry and firm fixed effects in further analysis, we find that significance of this premium dissipates. This suggests that the value contribution of FX derivative usage is rather a noisy proxy for the effect of omitted factors such as managerial quality, which could feasibly drive both FX derivative usage and firm value. Therefore, in this analysis, we find insubstantial evidence to support the notion that FX derivative usage improves firm value.